Perancangan dan Penerapan Sistem Informasi Maintenance dan Biaya Mesin di PT. XYZ - Apriyanto, Joni (JATISI, 2025)
Competition in the business world is getting tighter, including in the manufacturing industry. Companies that will survive are companies that can maximize machine capacity with the most efficient costs in their operations. PT. XYZ already has a maintenance information system to monitor machine performance but does not yet have a system to monitor costs incurred for machine maintenance and repairs so that it cannot find out machine performance in terms of costs. The purpose of this study is to complement the existing maintenance information system with an additional integrated cost monitoring system that helps the engineering department to find out the costs incurred in detail. The method used in this study is to conduct a survey of the existing system and plan a system that is able to find out machine costs in detail. The results of this study are a maintenance and machine cost information system that can be used well at PT. XYZ. This system is able to assess machine performance, engineering department performance and is able to find out the costs incurred in detail and the report data can be used for maintenance planning and spare part reserves in the engineering department.